Nursing Analysis of SEFT and PC6 Acupressure in Reducing Anxiety in Stemi Patients - Fitri Fitri; Zulmah Astuti; Ulfatul Muflihah; Dwi Widiyastuti (PT Inovasi Pratama Internasional, 2026)
Anxiety is one of the most common psychological responses experienced by patients with ST-Elevation Myocardial Infarction (STEMI) during hospitalization in the Intensive Cardiac Care Unit (ICCU), which may affect physiological stability and the recovery process. Therefore, supportive non-pharmacological nursing interventions are needed to help manage anxiety. This study aimed to analyze nursing practice through the application of the Spiritual Emotional Freedom Technique (SEFT) and PC6/Neiguan acupressure on anxiety levels in patients with STEMI. A case analysis was conducted on two patients with STEMI in the ICCU using a nursing care approach. The first patient received standard care combined with SEFT and PC6/Neiguan acupressure interventions, while the second patient received standard care only. Anxiety levels were measured using the State–Trait Anxiety Inventory (STAI). The patient who received SEFT and PC6/Neiguan acupressure experienced a reduction in anxiety level from moderate anxiety to no anxiety, while the patient who received standard care only did not show any reduction in anxiety level and remained in the moderate anxiety category. The application of SEFT and PC6/Neiguan acupressure in nursing practice was associated with reduced anxiety levels in patients with STEMI and may serve as supportive nursing therapies within a holistic nursing care approach for cardiovascular patients